ANALISIS KETERAMPILAN DASAR MENGAJAR GURU SEKOLAH DASAR (STUDI KASUS) PADA KELAS 3 UPT SEKOLAH DASAR - Silaban, Maria Kristina; Tanjung, Darinda Sofia; Abi, Antonius Remigius; Silaban, Patri Janson (Universitas Negeri Medan, 2023)
This research is research that examines in more depth how the teaching and learning process is carried out by teachers at UPT SDN 066650 Medan. Teachers are required to master eight basic teaching skills, namely: 1)opening and closing lesson skills, 2) explanation skills,3) variation skills, 4) questioning skills, 5) reinforcement skills, 6) class management skilss,7) group teaching skills small and individual, 8) skills in guiding small group discussions. Therefore, researchers tried to examine whether teachers implemented the eight basic teaching skills. This type of research is qualitative research-case study. The results of the research show that the eight basic teaching skills have almost implemented these basic teaching skills.